Wavumba : the man who believes in his stories - Velzen, Jeroen van; Kee, Sara; Studio Nieuwe Gronden; Eastwest Film Distribution GwBH ([Amsterdam, Netherlands] : SNG Film & Boeddhistische Omroep, 2012)
A Dutch, Kenyon-raised filmmaker seeks out the magical stories of his Kenyan childhood. Villagers and shamans tell ritual stories and tales of sea spirits, and the filmmaker follows Masoud, a legendary Kenyan fisherman known for catching giant sharks in his bare hands, while the two row out to sea, as Masoud tells his fish tales, discusses fishing techniques and flora and fauna, and becomes a guide to an intangible spirit world as they explore the holy islands, resting place of the spirits.
Cinematographer, Lennart Verstegen; editor, Stefan Kamp; music (guitar), Jeroen Schmohl.
Originally produced as a motion picture in 2012.
In English and Swahili with English subtitles.
Winner in the Tribeca Film Festival 2012: Best New Documentary Director
Online resource; title from opening/closing credits (Digitalia Film Library, viewed October 12, 2015).
Keywords: Tales -- Kenya; Fishers -- Kenya -- Drama; Fishing -- Kenya -- Drama; Shamans -- Kenya -- Drama; Spirits -- Drama; Documentary films; Nonfiction films; Feature films; Internet videos; Streaming video